Timing of ICSI with Respect to Meiotic Spindle Status - Tepla, Olga; Topurko, Zinovij; Jirsova, Simona; Moosova, Martina; Fajmonova, Eva; Cabela, Radek; Komrskova, Katerina; Kratochvilova, Irena; Masata, Jaromir (International journal of molecular sciences, 2022)
The aim of this study was to evaluate the efficiency of using meiotic spindle (MS) visibility and relative position to the polar body (PB) as indicators of oocyte maturation in order to optimize intracytoplasmic sperm injection (ICSI) timing. This was a cohort study of patients younger than 40 years with planned ICSI, the timing of which was determined by MS status, compared with those without MS evaluation. The angle between PB and MS and MS visibility were evaluated by optical microscope with polarizing filter. Oocytes with MS evaluation were fertilized according to MS status either 5-6 h after ovum pick-up (OPU) or 7-8 h after OPU. Oocytes without MS evaluation were all fertilized 5-6 h after OPU. For patients over 35 years visualization of MS influenced pregnancy rate (PR): 182 patients with MS visualization had 32% PR (58/182); while 195 patients without MS visualization had 24% PR (47/195). For patients under 35 years, visualization of MS did not influence PR: 140 patients with MS visualization had 41% PR (58/140), while 162 patients without MS visualization had 41% PR (66/162). Visualization of MS therefore appears to be a useful parameter for assessment of oocyte maturity and ICSI timing for patients older than 35.
Keywords: ICSI; těhotenství; Humans; lidé; human oocyte; meiotic spindle; Spindle Apparatus; polarized light microscopy; intracytoplazmatické injekce spermie; Female; Male; Semen; mužské pohlaví; gravidity; Cohort Studies; in vitro fertilization; polar body; ženské pohlaví; sperma; aparát dělícího vřeténka; Oocytes; kohortové studie; Sperm Injections, Intracytoplasmic; Pregnancy; oocyty